2017
DOI: 10.1111/jne.12470
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles for the amyloid precursor protein and derived peptides in the regulation of cellular and systemic metabolism

Abstract: The amyloid precursor protein (APP) is a transmembrane protein that can be cleaved by proteases through two different pathways to yield a number of small peptides, each with distinct physiological properties and functions. It has been extensively studied in the context of Alzheimer`s disease, with the APP-derived amyloid β (Aβ) peptide being a major constituent of the amyloid plaques observed in this disease. It has been known for some time that APP can regulate neuronal metabolism; however, the present review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…Consequently, the bloodstream becomes one of the major chronic supplies of Aβ peptides to the brain [31]. Both APP and its Aβ production pathway are involved in several cerebral physiological processes, such as neurotrophic activity, modulation of synaptic plasticity, neurogenesis, metal ion sequestration, antioxidant activity, and calcium homeostasis [32].…”
Section: Production Physiological Roles and Pathophysiological Consmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the bloodstream becomes one of the major chronic supplies of Aβ peptides to the brain [31]. Both APP and its Aβ production pathway are involved in several cerebral physiological processes, such as neurotrophic activity, modulation of synaptic plasticity, neurogenesis, metal ion sequestration, antioxidant activity, and calcium homeostasis [32].…”
Section: Production Physiological Roles and Pathophysiological Consmentioning
confidence: 99%
“…Aβ protein has an important physiological role, which can be dysregulated with aging or in AD [5,32]. Impairment of the balance between Aβ production and clearance leads to an accumulation of Aβ within the brain parenchyma or in the vessel walls, which can generate neurodegenerative processes leading to dementia [45].…”
Section: Aβ Clearancementioning
confidence: 99%
“…Therefore, Aβ peptide and tau protein are often considered as potential pharmacological targets. Amyloid precursor protein (APP) is cleaved by β-secretase 1, a beta-site APP cleaving enzyme 1, to produce Aβ peptide [ 2 ]. Presenilin 1 (PS1) is a part of γ-secretase complex which cleaves APP [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data obtained from Drosophila melanogaster suggest that fragmentation of behavioural rhythmicity is attributable to both α-and β-processing of APP (Blake et al 2015), which may further highlight the differences observed in energy balance and activity between the previously published BACE1-deficient mice vs APP KO mice from this study. These studies highlight the complexity in APP-mediated regulation of whole body energy homeostasis and as we have recently hypothesised, could indicate that peptides derived from the amyloidogenic and non-amyloidogenic processing of APP could have different effects on aspects of systemic metabolism (Czeczor & McGee 2017).…”
Section: Discussionmentioning
confidence: 62%